Policy for Arranging Tourist Destinations in North Minahasa Regency - Methalia, Methalia; Masengi, Evi E; Mokat, Jetty E.H (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Tourism development needs to pay attention to the availability of facilities and infrastructure to realize tourism development as an industry. Efforts to promote natural beauty and cultural riches abroad must also be supported by all existing infrastructure and facilities in the area being promoted. The aim of this research is to develop tourism which has been determined. It is hoped that it can spur tourism development in North Minahasa Regency. Tourism promotion has a big influence on the perceptions of foreign and domestic tourists regarding tourism conditions in North Minahasa Regency. The method used in this research is qualitative. This research seeks to provide a general overview of the Tourism Destination Arrangement Policy in North Minahasa Regency. Where there are still many problems that arise, regarding the process of structuring/managing existing tourist destinations. The results of the research obtained to create policies for structuring tourist destinations are influenced by several factors, one of which is Community Involvement. The development of the Special Economic Zone in Likupang, leads to the tourism sector where the development of Super Priority Destinations in Likupang is the central point of the development goal. Accessibility (Facilities and Infrastructure) and Determinant Factors.